Publication Trends for Alzheimer's Disease Worldwide and in China: A 30-Year Bibliometric Analysis - Dong, Rui; Wang, Hong; Ye, Jishi; Wang, Mingshan; Bi, Yanlin (Frontiers in Human Neuroscience, 2019)
Background: Alzheimer's disease, the most common form of dementia, has tremendous social and economic impact worldwide. This study aimed to analyze global trends in Alzheimer's disease research and to investigate China’s contribution to this research. Methods: The quantity and influence of publications related to Alzheimer's disease in China and elsewhere were compared. The Web of Science and PubMed databases were searched from 1988 to 2017 using the terms “Alzheimer's disease” or “Alzheimers disease.” Global Alzheimer's disease publications were classified and analyzed. Keywords, countries, and institutions publishing articles on Alzheimer’s disease were analyzed, and citations of these articles were examined. Results: A total of 181,116 articles regarding Alzheimer's disease research were identified and analyzed. Neuroscience and neurology were the main research categories both globally and in China. Basic research dominated Alzheimer’s publications, accounting for 30.93% of global publications and 95.31% of publications in China. A total of 8,935 journals published articles related to Alzheimer’s disease. The journal Neurobiology of Aging published the most Alzheimer’s disease-related articles, numbering 5,206 over the time period examined. The National Institutes of Health, the National Institute on Aging, and the Department of Health and Human Services jointly sponsored 11,809 articles, ranking first in the world. The National Natural Science Foundation of China funded the largest number of studies on Alzheimer's disease in China and recognized the importance of traditional Chinese medicine in Alzheimer’s disease research. Conclusions: The present study provides data for global researchers to understand research perspectives and develop future research directions. In recent years, Chinese researchers have contributed significantly to global Alzheimer’s research. Still, strengthening international cooperation could improve the quality and number of publications regarding Alzheimer’s disease.